A Cross-Generational Study of Contraception and Reproductive Health Among Sudanese and Eritrean Women in Brisbane, Australia - Rogers, Claire; Earnest, Jaya (Taylor & Francis Group LLC, 2014)
This study conducted in Brisbane, Australia, was undertaken with a cross-section of Sudanese and Eritrean mothers and daughters. We explored and documented the women’s intergenerational experiences and knowledge of reproductive health and contraception. Underpinned by a qualitative approach, focus group discussions were undertaken along with key informant interviews with health and multicultural sector professionals. Through examination of knowledge shared, the analysis distilled key aspects of intergenerational fears, cultural safety, and health. Participants proposed recommendations on how refugee and migrant women in Australia and resettled countries globally can more effectively and holistically exercise their sexual and reproductive health rights.